2014
DOI: 10.2478/s11535-014-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouses of botanical gardens as a habitat of alien and native macrofungi: a case study in Poland

Abstract: Abstract:In 2010, 16 macrofungi species were found in greenhouses of the Botanical Garden in Warsaw-Powsin. These included 8 species of lepiotaceous fungi and a few species known from warmer areas. For 3 species identified, which are new to Poland (Agaricus subrufescens, Leucocoprinus heinemannii, Marasmius teplicensis), a description is given, with drawings of their microscopic features and photographs. Species composition of macrofungi is compared in 5 complexes of greenhouses (Bayreuth, Graz, Jena, Paskov, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…On the other hand, knowledge on patterns of macrofungal invasions is geographically restricted (e.g. Szczepkowski et al, 2014; Wood, 2017) and biased towards mycorrhizal taxa (e.g. Dickie et al, 2017; Nuñez & Dickie, 2014; Vellinga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, knowledge on patterns of macrofungal invasions is geographically restricted (e.g. Szczepkowski et al, 2014; Wood, 2017) and biased towards mycorrhizal taxa (e.g. Dickie et al, 2017; Nuñez & Dickie, 2014; Vellinga et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among various groups of macrofungi developing in the greenhouses of Europe, the bulk of the data relate to a targeted study of the species composition of agaricoid fungi. A number of greenhouses located in the nemoral regions of Central Europe (Austria, Germany, Poland, and Czech Republic) were studied, in which the biodiversity of agaricoid fungi was assessed based on the presence of fruitbodies in the soil [6,7,10,14,[16][17][18][19]. It has been demonstrated that the number of fungal species in greenhouses is significantly less compared to natural conditions, and mainly local fungal species develop, and the proportion of non-native sub/tropical fungi varies in the range of 10-20% of the total number of species.…”
Section: Of 23mentioning
confidence: 99%
“…It has been demonstrated that the number of fungal species in greenhouses is significantly less compared to natural conditions, and mainly local fungal species develop, and the proportion of non-native sub/tropical fungi varies in the range of 10-20% of the total number of species. Agaricoid fungi in greenhouses are humus saprobes that have been sporadically found to be capable of exhibiting pathogenic or mycorrhizal activity [19,20]. The total number of agaricoid fungi in the greenhouses of these countries is 187 species.…”
Section: Of 23mentioning
confidence: 99%
“…& Thiers is an example of an additional alien species of mycobiota -besides Agaricus subrufescens Peck [1,2] and Aureoboletus projectellus (Murrill) Halling [3] -recorded in Poland in recent years. This fungus is known under a number of synonymous names: Boletus lakei Murrill, Boletinus lakei (Murrill) Singer, Ixocomus lakei (Murrill) Singer, and Suillus amabilis (Peck) Singer [4].…”
Section: Introductionmentioning
confidence: 99%